Promoting Potential Growth The Role of Structural Reform - de Mello, Luiz (OECD Economics Department Working Papers, 2010)
The global crisis has left many G20 countries with an unenviable legacy of lower potential output and high government indebtedness. Global imbalances, which had narrowed during the recession, are now beginning to widen again, as the recovery takes hold. Structural reform will be needed not only to recover the crisis-driven output loss and to maintain it in the longer term, but also to put the public finances back on a sustainable path and to rebalance global growth. To contribute to the policy debate, this paper summarises the analysis carried out by the OECD on the effects of a host of structural reforms on GDP growth, public finances and external current account balances